EXPERIMENTAL BASED DETERMINATION AND ANALYSIS OF MECHANICAL PROPERTIES OF AA 3003 ALLOY WELDED WITH FRICTION STIR LAP WELDING PROCESS - Dellal, Nabila; Merzoug, Mohammed; Mimmi, Abdelatif; Ghazi, Abdelkader; Lousdad, Abdelkader (Journal of Applied Engineering Science, 2023)
In recent years, friction stir welding (FSW) methods have been used to obtain good joints with mechanical and physical process properties. The development of FSW lap joint assembly will expand its use in ahigh number of industrial applications that can benefit from this technology. In this paper a study based on experimental methods were performed on FSW lap joints. The investigation includes the interface morphology and mechanical properties of the joint assembly. Experimental measurements were carried out on micro-hardness; tensile shear test, resulting material flow as well as the effect of flow variation on the obtained mechanical properties of FSW butt lap joints ofaluminium alloy AA3003. The study also presents the effects of different welding parameters on the lap joints assembly structure. It was found thatthe hardness in the welded region is significantly lower with respect to the base material.The fracture analysis shows the characteristics of ductile-brittle mixed fracture.
Keywords: friction stir welding, lap joint, aluminium AA3003, experimental measurements, parameters effects, tensile shear test, mechanical properties